Influence of bilateral nasal packing on sleep oxygen saturation after general anesthesia: A prospective cohort study - Guan, Shuwen; Zhao, Tingting; Ye, Jingying; Zhang, Junbo (Frontiers in Surgery, 2023)
Objective: To evaluate the effect of bilateral nasal packing on sleep oxygen saturation and it influencing factors on the first night after general anesthesia. Method: A total of 36 adult patients who underwent bilateral nasal packing with non-absorbable expanding sponge after general anesthesia surgery were prospectively studied. All these patients underwent overnight oximetry tests before and the first night after surgery. The following oximetry variables were collected for analysis: the lowest oxygen saturation (LSAT), the average oxygen saturation (ASAT), the oxygen desaturation index of ≥ 4% (ODI4), and the percentage of time with oxygen saturation below 90% (CT90). Results: Among the 36 patients, the incidences of both sleep hypoxemia and moderate to severe sleep hypoxemia increased with bilateral nasal packing after general anesthesia surgery. All the pulse oximetry variables we studied deteriorated significantly after surgery: both LSAT and ASAT decreased significantly (P<0.05), while both ODI4 and CT90 increased significantly (P < 0.05). In a multiple logistic regression analysis, body mass index (BMI), LSAT, and modified Mallampati grade were found to be independently predictive for a larger decrease in LSAT (≥5%) after surgery (all P < 0.05). Conclusion: Bilateral nasal packing after general anesthesia could induce or aggravate sleep hypoxemia, especially in patients with obesity, relatively normal sleep oxygen saturation, and high modified Mallampati grades.